A Comparative Bibliometric Analysis of Interdisciplinary Teaching Research in Chinese and International Literature - Zhao, Lei (Journal of Educational Research and Policies, 2026)
Interdisciplinary teaching has become an important approach for promoting curriculum integration and competency development. However, comparative studies on the research trends and knowledge structures of interdisciplinary teaching in different contexts remain limited. This study conducted a bibliometric analysis based on publications from CNKI and the Web of Science Core Collection (WoSCC). Using CiteSpace, publication trends, collaboration networks, keyword co-occurrence, clustering, and burst keywords were analyzed to identify research hotspots and emerging themes. The results show that interdisciplinary teaching research has grown steadily in both Chinese and international literature. Chinese studies mainly focus on curriculum reform, interdisciplinary thematic learning, instructional design, and artificial intelligence, while international studies emphasize STEM education, curriculum development, competency assessment, and empirical evaluation. The findings reveal different research orientations shaped by educational contexts and provide references for the future development of interdisciplinary teaching research.